Selection of Optimum Vegetative Indices for the Assessment of Tobacco Float Seedlings Response to Fertilizer Management. (26th July 2012) - Svotwa, Ezekia; Maasdorp, Barbara; Murwira, Amon; Masuka, Anxious
Abstract : The experiment sought to establish the vegetative indices for assessing tobacco float seedling varieties' response to different fertilizer rates. A factorial design, with 3 variety × 4 fertilizer management treatments, was used. The N : P : K treatments were applied at 7, 21, and 35 days after sowing, while N treatments were applied at 42 days. Radiometric measurements were taken at 49, 56, 64, and 79 days after sowing on 8 tray plots, using a multispectral radiometer. Mature seedling samples were harvested at day 79 and stem lengths were determined before processing for total N analysis. All the five channels of the radiometer, the NDVI, and the SRI had a strong relationship with fertiliser rate. Both the NDVI and SRI for T66 were greater (P < 0.05 ) than those for KRK26 and KE1. The SRI had a stronger relationship with seedling dry mass, seedling count/tray, and stem length than the NDVI. The NDVI also showed a stronger relationship with total N than the SRI. The minimum threshold SRI and NDVI values and optimum growth (100% fertilser) were 0.72 and 6.1. This information is useful in identifying and estimating tobacco seedbed area and seedling vigour using remote sensing and, therefore, is important in forecasting potential tobacco crop area and yield.